Implementasi Program Simpan Pinjam Perempuan (SPP) Di BUMDESMA Tirta Mandiri Kecamatan Tirtoyudo - Indriawati Indriawati; Sinnolah Sinnolah (Pakis Journal Institute, 2024)
Joint Village-Owned Enterprises (BUMDESMA) are business entities owned and managed by several or more villages. Law No. 6 of 2014 as the basis for the establishment of BUMDESMA. BUMDESMA is a forum for villages that have not been able to establish their own BUMDES. The Women's Savings and Loans Program of the Joint Village-Owned Enterprises (Bumdesma) Tirta Mandiri, Tirtoyudo District is the main topic of this research. The aim is to increase the benefits of the economic resources of the village community, increase the economy of the residents, and increase the original income of the village. This research uses a qualitative descriptive approach that includes interviews, observations, and documentation. The effectiveness and efficiency of its implementation are examined in this study. The research respondents were the community and Bumdesma administrators. Based on the results of this study, the Bumdesma Women's Savings and Loans program has a positive impact on the economy, investment, and productivity of the village community, as well as the emergence of various services and other types of businesses that contribute to community welfare. Bumdesma also develops savings and loans for women who have not been able to access banking and other activities that are oriented towards benefits that can be felt by as many people as possible in Tirtoyudo.